Pengaruh Model Learning Cycle 5E terhadap Kemampuan Kognitif IPA di Sekolah Dasar - Alvionita, Vani; silvinia, Silvinia; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
ABSTRACT The purpose of this study to determine the effect of the use of Learning Cycle 5E learning model to students' cognitive abilities in science learning in elementary school. The type of this research is Pseudo Experimental Research, with Posttest only control group design design. The population in this study are students of grade V SDN 06 Pauh Lubuk Sikaping. The result of data calculation using t-test at level α 0,05 obtained tcount> ttable that is 2,32029> 1,68. It can be concluded that there is a significant influence between the use of Learning Cycle 5E learning model to students' cognitive abilities on science learning in grade V SDN 06 pauh Lubuk Sikaping.Keyword: Learning Cycle 5E model, cognitive ability of IPA